Predicting the unprecedented: assessing contributions from large-scale modes of variability and climate change to Southeast Australia’s record spring rainfall in 2022 - Linjing Zhou; Eun-Pa Lim; Pandora Hope; Griffith Young; Acacia Pepler; Ian Simmonds (Climate Dynamics, 2026)
In September–November 2022, south-eastern Australia (SEA) experienced its wettest spring in the 126-year record, causing widespread and long-lasting flooding in the region. During this season, large-scale oceanic and atmospheric circulation conditions that generally drive SEA rainfall variations in spring were conducive to higher-than-normal rainfall over SEA: moderate La Niña and negative phase of the Indian Ocean Dipole (IOD) in the tropics and the positive phase of the Southern Annular Mode (SAM) in the Southern Hemisphere extratropics. The wet conditions occurred upon the background of long-term climate change in part due to increasing atmospheric greenhouse gases (GHGs). In this study, we focus on quantifying the portion of the 2022 SEA spring rainfall that can be explained by these large-scale climate drivers and anthropogenic global warming, using multiple linear regression and the Australian Bureau of Meteorology’s sub-seasonal to seasonal forecast system, ACCESS-S2, with modified initial conditions. Our statistical and dynamical modelling results show that the large-scale climate drivers and the GHG forcing could explain a substantial fraction of the record-high rainfall over SEA in spring 2022, though far from explaining the full amount. We have found that anthropogenic climate change contributed ~ 12% to the total rainfall and, while the tropical ocean conditions contributed to significantly wetter-than-average rainfall, the atmosphere played a key role in amplifying the extremity of the event, with: a zonal wavenumber one pattern featuring a high pressure anomaly south of Australia, record-strong thermal wind over Australia and more frequent rain-bearing mid-latitude weather systems during spring 2022.

The role played by the Indian Ocean High in affecting winter precipitation over Victoria, Australia - Saqib Ur Rehman; Ian Simmonds; Bilal Ahmed Usmani; Abdel Hannachi (Dynamics of Atmospheres and Oceans, 2024)

Impact of Pacific blocking on the intraseasonal winter sea ice seesaw between the Bering and Okhotsk Seas - Yao Yao; Wenqin Zhuo; Dehai Luo; Ian Simmonds; Binhe Luo; Linhao Zhong; Fei Huang (Atmospheric Research, 2024)

Different influences of La Niña types on the winter sub-seasonal Eurasian cold anomalies linked to Ural blocking - Binhe Luo; Yao Yao; Cunde Xiao; Dehai Luo; Ian Simmonds; Yina Diao; Wenqi Zhang; Yao Ge; Jiaqi Shi (Atmospheric Research, 2024)

The separate roles played by the two geographical poles of the NAO in influencing winter precipitation over Spain - Saqib Ur Rehman; Bilal Ahmed Usmani; Ian Simmonds (Journal of Atmospheric and Solar-Terrestrial Physics, 2023)

The key atmospheric drivers linking regional Arctic amplification with East Asian cold extremes - Wenqin Zhuo; Yao Yao; Dehai Luo; Ian Simmonds; Fei Huang (Atmospheric Research, 2023)

The modulation of Interdecadal Pacific Oscillation and Atlantic Multidecadal Oscillation on winter Eurasian cold anomaly via the Ural blocking change - Binhe Luo; Dehai Luo; Aiguo Dai; Ian Simmonds; Lixin Wu (Climate Dynamics, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

A Mediterranean cold front identification scheme combining wind and thermal criteria - Evangelia Bitsa; Helena A. Flocas; John Kouroutzoglou; George Galanis; Maria Hatzaki; George Latsas; Irina Rudeva; Ian Simmonds (International Journal of Climatology, 2021)
The goal of this study is to advance an automated and objective scheme for the identification of cold fronts over the Mediterranean based on wind‐related criteria, MedFTS, by further incorporating thermal criteria, in order to improve the identification of cold fronts on a climatological basis. These thermal criteria are related to cold advection and the thermal front parameter, and their individual or combined contribution is systematically investigated considering different threshold values. For each combination of thermal criteria and/or threshold values, the results are validated with the aid of statistical indices and metrics, and the optimum scheme configuration for the identification of Mediterranean fronts is selected. The advanced version of MedFTS, named MedFTS_DT, having incorporated both dynamic and thermodynamic criteria, is applied and validated for a decade of fronts over the Mediterranean. It was found that the number of erroneously identified cold fronts over Greece was significantly reduced from MedFTS to MedFTS_DT version by almost 40%, as indicated by the statistical metrics. Therefore, the performance of MedFTS_DT is verified to be superior to MedFTS. As a further attempt to investigate the ability of MedFTS_DT to perform adequate climatological analysis in the Mediterranean, the frequency of the cold fronts was calculated over Greece during the period 2007–2016 on a monthly and seasonal basis, demonstrating that the scheme can capture the intra‐annual variations. Finally, the contribution of the cold fronts to the precipitation over the Mediterranean for the same period was investigated, further supporting the scheme's performance.

Anchoring of atmospheric teleconnection patterns by Arctic Sea ice loss and its link to winter cold anomalies in East Asia - Muyuan Li; Dehai Luo; Ian Simmonds; Aiguo Dai; Linhao Zhong; Yao Yao (International Journal of Climatology, 2021)
In this paper, the physical processes underlying recent winter cold anomalies over East Asia (EA) are examined via statistical analysis. It is found that the EA cold anomaly depends on the warming in the North Atlantic, sea ice loss in the Barents–Kara Sea (BKS), and atmospheric teleconnection patterns. Specifically, the sea ice loss in the BKS can anchor teleconnection patterns originating from different North Atlantic sea surface temperature (SST) patterns. Different patterns of North Atlantic warming can affect the position of the cold anomaly region through altering the atmospheric circulations. In addition, whether the relevant teleconnection pattern leads to enhanced cold anomaly over EA crucially depends on the sea ice loss in the BKS, because it can anchor the blocking anticyclone embedded in the teleconnection pattern over the Ural region and make it more persistent and quasi‐stationary. Furthermore, it is found that the role of SST modes in the EA cold anomaly depends on their time scales. Although the strong basin‐scale warming (north–south SST tripolar mode) in the North Atlantic mid‐ to high‐latitudes plays a major role in decadal (interannual) cold anomaly over EA, it appears that the Atlantic east–west SST dipole structure dominates winter temperature variations over EA in recent decades on both the interannual and decadal time scales.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Links between Tasmanian precipitation variability and the Indian Ocean subtropical high - Saqib Ur Rehman; Kamran Khan; Ian Simmonds (Theoretical and Applied Climatology, 2019)

Taxonomy of the order Mononegavirales: update 2019 - Gaya K. Amarasinghe; María A. Ayllón; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Camila Chabi-Jesus; et al. (Archives of Virology, 2019)

Taxonomy of the order Mononegavirales: second update 2018 - Piet Maes; Gaya K. Amarasinghe; María A. Ayllón; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Kartik Chandran; et al. (Archives of Virology, 2019)

The winter midlatitude-Arctic interaction: effects of North Atlantic SST and high-latitude blocking on Arctic sea ice and Eurasian cooling - Binhe Luo; Lixin Wu; Dehai Luo; Aiguo Dai; Ian Simmonds (Climate Dynamics, 2019)

A saturated SNP linkage map for the orange wheat blossom midge resistance gene Sm1 - Mulualem T. Kassa; Sabrina Haas; Edgar Schliephake; Clare Lewis; Frank M. You; Curtis J. Pozniak; Ilona Krämer; Dragan Perovic; Andrew G. Sharpe; Pierre R. Fobert; Michael Koch; Ian L. Wise; et al. (Theoretical and Applied Genetics, 2016)

Sensitivity of the distribution of thunderstorms to sea surface temperatures in four Australian east coast lows - Christopher R. S. Chambers; Gary B. Brassington; Kevin Walsh; Ian Simmonds (Meteorology and Atmospheric Physics, 2015)

Large scale and sub-regional connections in the lead up to summer heat wave and extreme rainfall events in eastern Australia - Ghyslaine Boschat; Alexandre Pezza; Ian Simmonds; Sarah Perkins; Tim Cowan; Ariaan Purich (Climate Dynamics, 2015)

Precipitation changes due to the introduction of eddy-resolved sea surface temperatures into simulations of the “Pasha Bulker” Australian east coast low of June 2007 - Christopher R. S. Chambers; Gary B. Brassington; Ian Simmonds; Kevin Walsh (Meteorology and Atmospheric Physics, 2014)

Atmospheric impacts of Arctic sea-ice loss, 1979–2009: separating forced change from atmospheric internal variability - James A. Screen; Clara Deser; Ian Simmonds; Robert Tomas (Climate Dynamics, 2014)

Large scale features and energetics of the hybrid subtropical low ‘Duck’ over the Tasman Sea - Alexandre Bernardes Pezza; Luke Andrew Garde; José Augusto Paixão Veiga; Ian Simmonds (Climate Dynamics, 2014)

On the vertical structure of Mediterranean explosive cyclones - John Kouroutzoglou; Helena A. Flocas; Kevin Keay; Ian Simmonds; Maria Hatzaki (Theoretical and Applied Climatology, 2012)

Declining summer snowfall in the Arctic: causes, impacts and feedbacks - James A. Screen; Ian Simmonds (Climate Dynamics, 2012)

Climate links and recent extremes in antarctic sea ice, high-latitude cyclones, Southern Annular Mode and ENSO - Alexandre Bernardes Pezza; Harun A. Rashid; Ian Simmonds (Climate Dynamics, 2012)

Assessing characteristics of Mediterranean explosive cyclones for different data resolution - John Kouroutzoglou; Helena A. Flocas; Ian Simmonds; Kevin Keay; Maria Hatzaki (Theoretical and Applied Climatology, 2011)

Effect of tropospheric temperature change on the zonal mean circulation and SH winter extratropical cyclones - Eun-Pa Lim; Ian Simmonds (Climate Dynamics, 2009)

Climate perspective on the large‐scale circulation associated with the transition of the first South Atlantic hurricane - Alexandre Bernardes Pezza; Ian Simmonds; Augusto Jose Pereira Filho (International Journal of Climatology, 2009)
The landfall of Cyclone Catarina on the Brazilian coast in March 2004 became known as the first documented hurricane in the South Atlantic Ocean, promoting a new view on how large‐scale features can contribute to tropical transition. The aim of this paper is to put the large‐scale circulation associated with Catarina's transition in climate perspective. This is discussed in the light of a robust pattern of spatial correlations between thermodynamic and dynamic variables of importance for hurricane formation. A discussion on how transition mechanisms respond to the present‐day circulation is presented. These associations help in understanding why Catarina was formed in a region previously thought to be hurricane‐free. Catarina developed over a large‐scale area of thermodynamically favourable air/sea temperature contrast. This aspect explains the paradox that such a rare system developed when the sea surface temperature was slightly below average. But, although thermodynamics played an important role, it is apparent that Catarina would not have formed without the key dynamic interplay triggered by a high latitude blocking. The blocking was associated with an extreme positive phase of the Southern Annular Mode (SAM) both hemispherically and locally, and the nearby area where Catarina developed is found to be more cyclonic during the positive phase of the SAM. A conceptual model is developed and a ‘South Atlantic index’ is introduced as a useful diagnostic of potential conditions leading to tropical transition in the area, where large‐scale indices indicate trends towards more favourable atmospheric conditions for tropical cyclone formation. Copyright © 2008 Royal Meteorological Society

Southern hemisphere cyclones and anticyclones: recent trends and links with decadal variability in the Pacific Ocean - Alexandre Bernardes Pezza; Ian Simmonds; James A. Renwick (International Journal of Climatology, 2007)
The aim of this paper is to study the association between the extratropical Southern Hemisphere and the decadal variability in the Pacific Ocean (PO). We discuss a pattern of coherent large‐scale anomalies and trends in cyclone and anticyclone behaviour in light of the climate variability in the PO over the ERA40 reanalysis period (1957–2002). The two representative PO indices are the Pacific Decadal and Interdecadal Oscillations (PDO and IPO), and here the PDO is chosen owing to it being less associated with the southern oscillation index (SOI). Composites of the indicators of the density and intensity of cyclones/anticyclones given by an automatic tracking scheme were calculated for the years when the PDOI was more than one standard deviation above or below its mean. Although the ERA40 is not free from noise and assimilation changes, the results show a large‐scale feature, which seems to be robust and agrees with earlier studies using different data sets. The sea‐level pressure shows a strong annular structure related to the PDO, which is not seen for the SOI, with lower pressure around Antarctica during the positive phase and vice versa. More intense (and fewer) cyclones and anticyclones were observed during the positive PDO. This is less consistent for the SOI, particularly during the summer when a different PDO/SOI pattern arises at high latitudes. The trends project a pattern coincident with the positive PDO phase and seem to be linked with the main climate shift in the late seventies. Trends observed over the Tasman Sea are consistent with declining winter rainfall over southeastern Australia. Most patterns are statistically significant and seem robust, but random changes in ENSO may play a part, to a certain degree, in modulating the results, and a physical mechanism of causality has not been demonstrated. Although global warming and related changes in the Southern Annular Mode (SAM) may also help explain the observed behaviour, the large‐scale response presented here provides a new insight and would be of considerable interest for further modelling studies. Copyright © 2007 Royal Meteorological Society

Association between Australian rainfall and the Southern Annular Mode - Belinda Meneghini; Ian Simmonds; Ian N. Smith (International Journal of Climatology, 2007)
In this study, we explore the relationships between seasonal Australian rainfall and the Southern Annular Mode (SAM). We produce two seasonal indices of the SAM: the Antarctic Oscillation Index (AOI), and an Australian regional version (AOIR) using ERA‐40 mean sea‐level pressure (MSLP) reanalysis data. The seasonal rainfall data are based on gridded monthly rainfall provided by the Australian Bureau of Meteorology. For the period 1958–2002 a significant inverse relationship is found between the SAM and rainfall in southern Australia, while a significant in‐phase relationship is found between the SAM and rainfall in northern Australia. Furthermore, widespread significant inverse relationships in southern Australia are only observed in winter, and only with the AOIR. The AOIR accounts for more of the winter rainfall variability in southwest Western Australia, southern South Australia, western and southern Victoria, and western Tasmania than the Southern Oscillation Index. Overall, our results suggest that changes in the SAM may be partly responsible for the current decline in winter rainfall in southern South Australia, Victoria, and Tasmania, but not the long‐term decline in southwest Western Australian winter rainfall. Copyright © 2006 Royal Meteorological Society.

Large-scale Vertical Momentum, Kinetic Energy and Moisture Fluxes in the Antarctic Sea-ice Region - Ian Simmonds; Anthony Rafter; Timothy Cowan; Andrew B. Watkins; Kevin Keay (Boundary-Layer Meteorology, 2005)

Distribution and temporal variability of 500 hPa cyclone characteristics in the Southern Hemisphere - Murray Keable; Ian Simmonds; Kevin Keay (International Journal of Climatology, 2002)
A 40 year period (1958–97) of US National Centers for Environmental Prediction reanalysis data has been used to diagnose the behaviour and variability of 500 hPa extratropical cyclones for the Southern Hemisphere using a Lagrangian perspective. The ‘finding’ and ‘tracking’ of these systems were performed using a fully automated scheme. Seasonal distributions of system density, cyclone formation (cyclogenesis), decay (cyclolysis), cyclone centre velocity and intensity/strength are presented. System density is shown to exhibit a maximum in the surface circumpolar trough region and over the Antarctic continent. A broad band of enhanced cyclone system density was evident across the South Pacific from southeast Australia to South America in all seasons, most markedly in winter. As this feature appears also at the surface level, strong vertical consistency of these cyclones in the low and middle troposphere is indicated. Velocities of cyclone centres were found to peak in the latitudes 50–55 °S, and 500 hPa systems appeared to move on average in a much more zonal (easterly) direction than their sea‐level counterparts. The mean number of midlatitude cyclones per analysis has exhibited a significant downward trend over the record, with particularly low values observed in the early 1980s. Offsetting this trend have been increases in three measures of mean cyclone vigour. Three orographic features, in particular, are seen to influence the behaviour of 500 hPa cyclones: the mountains of New Zealand, the Antarctic Peninsula and the southern Andes. Over most of Antarctica the rate of cyclogenesis exceeds that of cyclolysis, indicating that many of the cyclones being formed in the vortex are actually exported out (i.e. to the north) of the continent. In the subtropics, considerable numbers of systems are formed in the Mozambique Sea region, but these tend to be quasi‐stationary features. Copyright © 2002 Royal Meteorological Society.

Seasonal and regional responses to changes in Australian soil moisture conditions - Ian Simmonds; Pandora Hope (International Journal of Climatology, 1998)

Seasonal and regional responses to changes in Australian soil moisture conditions - Ian Simmonds; Pandora Hope (International Journal of Climatology, 1998)

The mean structure and temporal variability of the semiannual oscillation in the southern extratropics - Ian Simmonds; David A. Jones (International Journal of Climatology, 1998)

Persistence Characteristics of Australian Rainfall Anomalies - Ian Simmonds; Pandora Hope (International Journal of Climatology, 1997)

INTERANNUAL VARIABILITY OF SOUTH-EASTERN AFRICAN SUMMER RAINFALL. PART II. MODELLING THE IMPACT OF SEA-SURFACE TEMPERATURES ON RAINFALL AND CIRCULATION - ALFREDO ROCHA; IAN SIMMONDS (International Journal of Climatology, 1997)

INTERANNUAL VARIABILITY OF SOUTH-EASTERN AFRICAN SUMMER RAINFALL. PART 1: RELATIONSHIPS WITH AIR–SEA INTERACTION PROCESSES - ALFREDO ROCHA; IAN SIMMONDS (International Journal of Climatology, 1997)

AN ANALYSIS OF ANTARCTIC SEA-ICE AND EXTRATROPICAL CYCLONE ASSOCIATIONS - CHRISTOPHER R. GODFRED-SPENNING; IAN SIMMONDS (International Journal of Climatology, 1996)

SUB-GRID-SCALE TOPOGRAPHY AND THE SIMULATION OF NORTHERN HEMISPHERE SNOW COVER - DAVID J. WALLAND; IAN SIMMONDS (International Journal of Climatology, 1996)